Saints and Sinners:: Popular Myth and the Study of the Personalities of the Antigonish Movement - Ludlow, Peter (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2013)
The narrative of the St. Francis Xavier University Extension Department has long been styled as an exchange between “saints and sinners.” Beginning in the 1930s, journalists, writers, and historians wrote of the leading saint, Fr. James J. Tompkins, and his struggle against the foremost sinner, Archbishop James Morrison, which resulted in the priest’s exile to Canso in 1922 and ultimate redemption as the spiritual father of Antigonish Movement.  Exploring aspects of the Extension story, this article examines the “saints and sinners” myth and illustrates the effect that it has had on the history of the movement.